Profesionalisme Dalam Pendidikan Islam - Sumarno, Sumarno (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Ilmu Tarbiyah Muhammadiyah Tempurrejo Ngawi, 2019)
Every school is required to be creative, innovative and consistent to uphold Islamic values and the value of professionalism through a directed institution development program. Every school should be able to develop professional attitudes both in and out. Into the means of creating experts for the school principal, teachers and employees, while out means able to capture opportunities and cooperation with the community so that the school is financially and socially will be strong. Furthermore, the professionalism of the school must be developed based on the principle of openness so that the internal parties (teachers and employees) and external (society) can be easily to participate in developing, giving input and evaluating school work. Keyword : professionalism, islamic education